Manual Acupuncture Effect on Vertigo and Tinnitus in Patient with Labyrinthitis: A Case Report - Cindy Notonegoro; Christina Simadibrata (Faculty of Medicine, University of Jember, 2021)
Labyrinthitis is an inflammatory disease of the inner ear perilymphatic cavity and the most common cause of prolonged spontaneous vertigo. Other symptoms are tinnitus and sensorineural hearing loss. Acupuncture is one of the non-pharmacological therapeutic modalities to improve symptoms of labyrinthitis. A 54-year-old woman complained of vertigo that is preceded by tinnitus in both ears since the last 6 months. She was diagnosed with labyrinthitis. Had taken amoxicillin and decadryl for 5 days, betaserc and dimenhydrinate when she felt dizzy, and amlodipine as a routine drug for her hypertension. Physical examination showed vital signs within normal limits, grade 2 obesity, positive Romberg test, and THI score 18. Manual acupuncture was performed at acupoints GV20, GB20, TE17, TE21, SI19, GB2, GB8, TE5, LI4, KI3, PC6 and LR3 with 20 minutes retention. After the first therapy, vertigo complaints disappeared and after 12 treatments (twice a week), frequency and intensity of tinnitus became less, with THI score of 6. Therefore, acupuncture can relieve vertigo and improve tinnitus which can be seen by a decrease of THI score. Keywords: acupuncture, labyrinthitis, tinnitus, vertigo